Dispersion-Tuned Mode-Locked Laser for Swept Source OCT at 850 nm Using a cFBG and the Pulse Modulation Technique - Rene Riha; Alejandro Martinez Jimenez; Gopika Venugopal; Marie Klufts; Robert Huber; Adrian Podoleanu (IEEE Photonics Journal, 2024)
In this paper, the feasibility of employing a fast intensity modulator and a chirped fibre Bragg grating to build a dispersion-tuned mode-locked swept laser (DTML-SS) for OCT at 850 nm is evaluated. Stable mode-locking is achieved by applying 50 ps pulses at 1 GHz to the modulator, obtaining 35 nm tuning range at 10 KHz sweep rate and 1 mm axial range.